The Effect Of Giving Pudding Seeds Of Yellow Pumpkin And Papaya On Nutritional Status In The Working Area Of The Puskesmas Gilingan - Noviyanti, Retno Dewi; Rahmawati, Tuti; Rachmawatiningsih, Rachmawatiningsih (Sean Institute, 2022)
Condition nutrition not enough will influence many organs and systems Because often accompanied with deficiency intake substance nutrition much needed macro and micro for body . For improve nutritional status toddler nutrition not enough there is a number of way one of them that is with seed pumpkin yellow and papaya . Objective study For know influence gift pudding seed pumpkin yellow and papaya on nutritional status in toddlers nutrition less in the Work Area Public health center mill . Research design use design experimental with approach two group pretest- posttest design . A total of 22 people became sample study with age 24-59 months , taking sample using purposive sampling. Data analysis used the Wilcoxon test. Research results This is the average nutritional status toddler before and after treatment group is -2,293 ± 0.32 SD and -1.889 ± 0.47 SD. Average nutritional status toddler before and after control group are -2.23±0.28 SD and -2.09±0.354 SD. Different test results before and after gift group treatment (p=0.007), before and after gift group control (p=0.047). Research conclusion This is there is influence gift pudding seed pumpkin yellow and papaya on nutritional status in toddlers nutrition less .